New Insights into Polychaete Traces and Fecal Pellets: Another Complex Ichnotaxon? - Kantimati G Kulkarni; Rajani Panchang (PLoS ONE, 2015)
Neoichnological observations help refine paleoichnological records. The present study reports extensive observations on the distribution, morphology, occurrence and association of burrows and fecal pellets of the polychaete Nereis diversicolor in the Kundalika Estuary on the west coast of India. Our holistic study of these modern-day traces suggests it to be a complex trace arising from domichnial, fodinichnial and possibly pascichnial behavior of polychaetes. The study for the first time reports extensive fecal pellet production, distribution and their preservation as thick stacks in modern estuarine environment. These observations testify the fossilization potential of pellets and provide an explanation to their origin in the geological record. Their occurrence as strings associated with mounds not only suggests pascichnial behaviour of polychaetes but also allows the assignment of post-Paleozoic Tomaculum to the activity of polychaete worms. The production of fecal pellets in such large quantities plays a major role in increasing the average grain size of the substrate of these estuarine tidal flats, thereby improving aeration within the substrate.